Contested psychiatric ontology and feminist critique: ‘Female Sexual Dysfunction’ and the Diagnostic and Statistical Manual - Angel, Katherine (History of the Human Sciences, 2012)
In this article I discuss the emergence of Female Sexual Dysfunction (FSD) within American psychiatry and beyond in the postwar period, setting out what I believe to be important and suggestive questions neglected in existing scholarship. Tracing the nomenclature within successive editions of the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM), I consider the reification of the term ‘FSD’, and the activism and scholarship that the rise of the category has occasioned. I suggest that analysis of FSD benefits from scrutiny of a wider range of sources (especially since the popular and scientific cross-pollinate). I explore the multiplicity of FSD that emerges when one examines this wider range, but I also underscore a reinscribing of anxieties about psychogenic aetiologies. I then argue that what makes the FSD case additionally interesting, over and above other conditions with a contested status, is the historically complex relationship between psychiatry and feminism that is at work in contemporary debates. I suggest that existing literature on FSD has not yet posed some of the most important and salient questions at stake in writing about women’s sexual problems in this period, and can only do this when the relationship between ‘second-wave’ feminism, ‘post-feminism’, psychiatry and psychoanalysis becomes part of the terrain to be analysed, rather than the medium through which analysis is conducted.
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; europe; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Y a-t-il un « cycle de la violence antiféministe »?: Les effets de l’antiféminisme selon les féministes québécoises - Blais, Mélissa (Recherches féministes, 2012)
S’appuyant sur la recherche Les attaques antiféministes, menée en partenariat avec L’R des centres de femmes du Québec, l’auteure documente les actions antiféministes et analyse leurs effets sur le mouvement féministe québécois. Inspirée par l’hypothèse de L’R des centres de femmes, selon laquelle les féministes réagissent à la violence antiféministe comme les femmes violentées en contexte conjugal et postconjugal, l’auteure se demande s’il existe un « cycle de la violence antiféministe ». À l’aide de la théorie du « cycle de la violence conjugale » et des études féministes sur les violences masculines contre les femmes, elle observe les similitudes entre les effets de la violence conjugale et les effets de la violence antiféministe, mais aussi les limites de l’analogie inhérentes aux dimensions collectives des attaques antiféministes.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; antiféminisme; approches et analyses; canada; cours; discipline; histoire et politique; pol4102; pol5185; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; violences

Elles eurent beaucoup d'enfants– et se marièrent histoire d'une famille homoparentale - Blanc, Myriam (Bec en l'air, 2012)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; filiation; france; hétérosexisme; identités LGBTQIA2+; mariage; maternité; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

À propos des rapports sociaux de sexe. - Kergoat, Danièle (Se battre, disent-elles .., 2012)
Recueil de textes de cette figure du féminisme et pionnière de la sociologie du travail et du genre en France. Il éclaire la construction d'analyses et de concepts autour de la division sexuelle du travail, des rapports sociaux de sexe, leur intrication avec les rapports de classe et de race. L'ensemble permet de retracer le chemin intellectuel et politique de D. Kergoat.
Section: 1 vol. (354 p.) : couv. ill. en coul., tabl. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail